Celebrity Endorsements and Voter Emotions: Evidence From Two Experiments. (July 2017) - Nownes, Anthony J.
Here, I report the results of two randomized, posttest only, control group, survey experiments in which respondents were exposed to factual information about celebrity support for Hillary Clinton during the 2016 presidential election campaign. Based on previous research, I hypothesize that celebrity endorsements will affect the emotions of enthusiasm, anger, and anxiety vis-à-vis Secretary Clinton. My results provide support for the general notion that celebrity endorsements can affect voter emotions. Specifically, I find that celebrity endorsements profoundly decreased the negative emotions of anger and anxiety vis-à-vis Secretary Clinton. My research suggests that a broad range of stimuli may affect voter emotions, which in turn affect political attitudes and behavior.